Physicians’ income in Brazil: a study on information sources - Scheffer,Mário (2022)
SUMMARY OBJECTIVE: Data on physicians’ income are relevant for well-informed health policies, both due to their strategic role and the volume of resources that their activities represent to health systems. In Brazil, multiple sources of data measure the income of these professionals, each one with singularities that generate a complex and heterogeneous picture. This study explores the methodological aspects of different data sources, pointing to potentials and limitations to measuring the income of physicians. METHODS: We use the sources’ documentation and data on the average monthly income in 2019, by gender and macro region, from four distinct surveys: Continuous Pnad (National Household Sample Survey), RAIS (Annual Listing of Social Information), Medical Demographics, and IRPF (Personal Income Tax). RESULTS: The results confirm the heterogeneity of definitions, variables, and methodologies. The data set can evidence phenomena such as the income difference between men and women. Regional inequalities are evident; however, the data interpretation is less assertive. CONCLUSIONS: Although eventual gaps and discrepancies among sources can limit some strong conclusions, the analysis of different methodologies employed can suggest relevant hypotheses for in-depth studies.